3 - L’intérêt de l’analyse du genre dans la relation économique entre la femme rurale et son environnement: le cas de Niadiène en Moyenne Casamance: by Aminata Sow - Aminata Sow (Africa Development, 1995)
This paper analyses the role of rural womens in the economic development process. The paper provides a description of the socio-economic conditions of the target-village focussing on the situation of women who are pushed into the background in the management of development projects ' initiated in this region. The author uses the rapid rural appraisal method which consists of discussing with the peasants about their different concerns and trying along with them to find adequate solutions and actions to be taken. The inquiry reveals that ecological, economic and demographic transformations are affecting living conditions. Finally she suggests the development of appropriate infrastructures and the questioning of 'malestream' discourse.